The Influence of Organizational Culture, Job Stress on Turnover Intention with Job Satisfaction as an Intervening Variable - Natasya Milleny; I Gede Adiputra (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
One of the human resource problems faced by startup companies is the high turnover intention of employees working in their companies. Turnover is an actual problem faced by various companies from various industrial and business lines. The purpose of this study is to analyze the influence of organizational culture and Work Stress on Turnover Intention in star up companies in Jakarta. The object of this study consists of 125 selected responses by purposive sampling. The results of this study can be concluded that organizational culture has a negative and significant influence on employee turnover intention in startup companies in Jakarta, organizational culture has a positive and significant influence on job satisfaction, work stress has a positive and significant influence on turnover intention Employees, work stress has a negative and significant influence on employee job satisfaction, job satisfaction has a negative and insignificant influence on employee turnover intention, organizational culture has a negative and significant influence on turnover intention through job satisfaction employees, as well as work stress have a positive and significant influence on turnover intention through employee job satisfaction at startup companies in Jakarta